The Effectiveness of Discovery Learning-Based Electronic Pocket Book Media to Improve Student Learning Outcomes on Chemical Bonding Materials - Sembiring, Julia Marantika; Silaban, Saronom (Journal of Science and Science Education, 2025)
This research aims to develop an electronic pocket book media based on Discovery Learning on class X chemical bond materials at SMA Negeri 1 Tanjung Morawa. Discovery learning was chosen because it encourages students to be actively involved in the learning process through exploration. The development model used in this study is the ADDIE model, which includes five stages, namely: analysis, design, development, implementation, and evaluation. The results of the study showed that the discovery learning-based electronic pocket book media had very good validity with a material feasibility percentage of 94.5% and 97.5% media feasibility based on expert assessments. In terms of effectiveness, it has proven to be quite effective with an N-Gain percentage of 74%. In conclusion, the discovery learning-based electronic pocket book media on chemical bonding materials is considered valid, effective, and practical in improving understanding of chemical concepts and student learning outcomes